AN APPLICATION OF LIQUID ORGANIC FERTILIZER FOR THE GROWTH AND PRODUCTION OF PAKCOY (Brassica rapa L) ON CHICKEN MANURE AND CHARCOAL GROWTH MEDIA - Sitorus, Doni Ardiansyah; Siregar, Maimunah; Z.N.A., Hanifah Mutia (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2020)
Pakcoy(Brassica rapa L) is an annual plant originating from the Brassica species which is easy to obtain at an economical price and contains ingredients needed by humans such as minerals, vitamins and fiber. This study aims to determine the response of water hyacinth liquid organic fertilizer and chicken manure compost planting medium with husk charcoal to the growth and production of pakcoy (B. rapa L). This research was conducted at Jalan Ikan Bandeng, Tanah Tinggi Village, East Binjai District, Binjai City using a Factorial Randomized Block Design (RBD) consisting of 2 factors, 16 combinations and 2 repetitions. The treatment of growing media (M) was 4 levels, namely: M0 = Control, M1 = 1:1 (Charcoal + Chicken Manure Compost), M2 = 2:1 (Charcoal + Chicken Manure Compost) and M3 = 1:2 (Charcoal rice husk + chicken manure compost). There are 4 levels of water hyacinth liquid organic fertilizer (P), namely: P0 = control (using plain water), P1 = 60 ml/500 liters of water/polybag, P2 = 120 ml/500 liters of water/polybag, and P3 = 180 ml /500 liters of water/poly bag. Parameters observed were plant height, number of leaves, leaf area per sample, production weight per plot, plant fresh weight per sample and net consumption weight per sample. The results of the research on planting media of chicken manure compost with rice husk charcoal had a significant effect on all observed parameters. The results of the study applying water hyacinth liquid organic fertilizer had no significant effect on the parameters of plant height, number of leaves, leaf area, net weight consumed per sample, fresh weight of plants per sample and had a significant effect on the parameter of production weight per plot.